Central Bank Independence - the Case of the National Bank of Republic of Macedonia - Anita Angelovska Bezhoska (Journal of Central Banking Theory and Practice, 2017)
This paper explores the level of independence of the National bank of the Republic of Macedonia by primarily focusing on the legal provisions that pertain to the key aspects for achieving and maintaining price stability. It provides a historical perspective of the evolution of the independence since the first years of transition. The assessment of the independence of the NBRM is based on the index of Cukierman, Webb, and Neyapti (1992), as one of the most commonly used indices, and the index of Jacome and Vazquez (2005), which incorporates some specific aspects relevant for transition economies. Both indices indicate that the legal independence of the NBRM has increased over the years and that the current legal framework provides a high level of independence. Yet, it should be emphasized that there is a room for further strengthening, in particular in the areas of policy formulation and the process of appointment of the non-executive members of the council of the NBRM. As the indices are based on the legal provisions, they can serve only as an indication of the actual independence of the central bank.
Keywords: E42; E58; 330; central bank independence; monetary policy; indices; Macedonia